Soil Particle Settlement Sorting and Distribution Characteristics of Carbon, Nitrogen and Salt During Gradual Thawing - Yuan Xinhao; Wang Xinyao; Li Fan; Wang Ruiqi; Hu Yaxian; Li Xianwen (Shuitu baochi tongbao)
[Objective] The classification of sediment particles and the accompanying distribution characteristics of carbon, nitrogen and salt in the process of soil thawing layer by layer under snowmelt runoff scenario were analyzed in order to identify the mechanism of soil freeze-thaw erosion and the induced micro-environmental effects on eroding slopes. [Methods] Soil samples were obtained from an eroding slope in the mollisol region of Northeastern China. Air-dried soil was used to fill columns that were subjected to three treatments: non-freeze-thaw, full freeze-full thaw, and gradual progressive thawing after freezing. The soil columns were completely immersed in a water bath so that thawing occurred from outside to inside. All soil samples were then fractionated by settling velocity, and the electrical conductivity (EC), pH value, soil organic carbon (SOC), and total nitrogen (TN) of each particle size were determined and analyzed. [Results] ① The freeze-thaw process reduced the proportion of the soil particles >500 μm and ≤125 μm, but increased the proportion of soil particles between 125 μm and 500 μm. Larger particles had higher EC, but lower SOC and TN. ② Across gradual progressively thawed layers, the outer layer (thawed earlier) had fewer particles ≤63 μm, and the inner layer (thawed later) had more particles between 125 μm and 500 μm. More specifically, EC, SOC, and TN were higher in the larger fractions from the outer layer. ③ Compared with the original soil, 64.8% of the dissolved solids were lost from the soil that experienced gradual progressive thawing, but the loss rate of SOC and TN was only 4.08% and 2.72%, respectively. The loss of dissolved solids and organic matter was greater from the inner layer than from the outer layer. [Conclusion] After freezing and thawing, the degree of fragmentation of the outer layer of soil was large, and the soil particles on the slope tended to become homogenized. Organic matter content varied significantly between particle size classes, and its distribution was more stable in small-grained soils. Salts and organic matter migrated from the inner layer of the soil to the outer layer during the freeze-thaw process, resulting in loss.